2013
DOI: 10.1177/1934578x1300801109
|View full text |Cite
|
Sign up to set email alerts
|

Ecology- and Bioassay-Guided Drug Discovery for Treatments of Tropical Parasitic Disease: 5α,8α-Epidioxycholest-6-en-3β-ol Isolated from the Mollusk Dolabrifera dolabrifera Shows Significant Activity against Leishmania donovani

Abstract: An ecology-and bioassay-guided search employed to discover compounds with activity against tropical parasitic diseases and cancer from the opisthobranch mollusk, Dolabrifera dolabrifera, led to the discovery of antileishmanial properties in the known compound, 5α,8α-epidioxycholest-6-en-3β-ol (1). Compound 1 was identified through nuclear magnetic resonance spectroscopy (1 H, 13 C) and mass spectrometry. The compound was concentrated in the digestive gland of D. dolabrifera, but was not detected in other body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…882 The search for new leads for the treatment of leishmaniasis has identied the known 5a,8a-epidioxycholest-6-en-3b-ol (Dolabrifera dolabrifera) as mildly active against the amastigote form with nearly sixty-fold selectivity versus Vero cells. 883 The structure of furan 1099 (Hypselodoris jacksoni, S. E. Queensland) was conrmed and absolute conguration established by a thorough study using combinations of synthesis, chiral HPLC and MPA derivatisation. 884 A new enantioselective route to oxazinin alkaloids (Mytilus galloprovincialis) 885,886 has helped conrm the absolute conguration of amongst others, oxazinin-1 and -2.…”
Section: Molluscsmentioning
confidence: 99%
“…882 The search for new leads for the treatment of leishmaniasis has identied the known 5a,8a-epidioxycholest-6-en-3b-ol (Dolabrifera dolabrifera) as mildly active against the amastigote form with nearly sixty-fold selectivity versus Vero cells. 883 The structure of furan 1099 (Hypselodoris jacksoni, S. E. Queensland) was conrmed and absolute conguration established by a thorough study using combinations of synthesis, chiral HPLC and MPA derivatisation. 884 A new enantioselective route to oxazinin alkaloids (Mytilus galloprovincialis) 885,886 has helped conrm the absolute conguration of amongst others, oxazinin-1 and -2.…”
Section: Molluscsmentioning
confidence: 99%
“…( Carbone et al, 2013 ). An anti-leishmaniasis compound, 5 α , 8 α -epidioxycholest-6-en-3 β -ol was characterized from Dolabrifera dolabrifera ( Clark et al, 2013 ). Mycosporine-type of amino acids 26 – 28 were isolated from the protective ink of Aplysia californica (Sea hare) ( Kamio, Kicklighter, Nguyen, Germann, & Derby, 2011 ).…”
Section: Bioactive Secondary Metabolites From Marine and Estuarine Momentioning
confidence: 99%
“…Among the few studies addressing its biological activity, Minh et al reported a strong cytotoxic effect against various cancer cell lines, namely human epidermoid carcinoma (KB), fibrillary sarcoma of uterus (FL), and human hepatocellular carcinoma (HepG-2) with IC 50 values of 4.8, 9.4, and 5.8 µM, respectively [13]. More recently, Clark et al found antileishmanial properties towards the amastigote form of Leishmania donovani , displaying an IC 50 of 4.9 µM [14].…”
Section: Introductionmentioning
confidence: 99%